2020
DOI: 10.1093/jac/dkaa143
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids of novel incompatibility group IncpRBL16 from Pseudomonas species

Abstract: Objectives To dissect genomic features of IncpRBL16 plasmids from Pseudomonas. Methods An extensive genomic comparison was applied to all 17 available sequenced IncpRBL16 plasmids, including 8 sequenced in this study and another 2 sequenced in two of our previous studies. Results Conserved IncpRBL16 backbone markers repAIncpRBL16 together with its iterons, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…These hypotheses explain the abundance of ISs in bacteria, which are influenced by drift, the frequency of HGT interactions, the positive or negative fitness effects of ISs, and, most importantly, the rate of transposition (808). (826)(827)(828)(829). Remarkably, these elements are the main vehicles of class 1 (Tn402) and class 2 (Tn7) integrons (717,(830)(831)(832).…”
Section: Ecology and Evolution Of Mobile Genetic Elementsmentioning
confidence: 99%
“…These hypotheses explain the abundance of ISs in bacteria, which are influenced by drift, the frequency of HGT interactions, the positive or negative fitness effects of ISs, and, most importantly, the rate of transposition (808). (826)(827)(828)(829). Remarkably, these elements are the main vehicles of class 1 (Tn402) and class 2 (Tn7) integrons (717,(830)(831)(832).…”
Section: Ecology and Evolution Of Mobile Genetic Elementsmentioning
confidence: 99%
“…pNDTH10366-KPC and pWTJH12-KPC belonged to a megaplasmid family[49, 50], referred as Type 2 plasmid here. As with other family members, these two plasmids carried a ParB-related ThiF-related cassette (PRTRC system), a chemotaxis operon, a partition system, a type II secretion system, a radical SAM operon, a tellurite resistance operon and a T4SS on its backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Tn6848, Tn6849, Tn6882, and Tn6883 were inserted within Tn6853, Tn6854, Tn6877, and Tn6878, respectively. Two chromosome-borne MGEs-the previously characterized mer-carrying unit transposon Tn6488 (Jiang et al, 2020) found in the isolates YT12746 and YTSEY8, and the IME Tn6779 (carrying no resistance genes; unrelated to this study) from the SE5357 isolatewere excluded.…”
Section: Comparison Of Five Related Ices Tn6417 Tn6584 Tn6585 Tn65mentioning
confidence: 99%
“…Besides, a 31.9-kb fragment composed of Tn6830, a truncated ISCR3-tetA(G)-cmlA9 unit, an empty integron In0 and IS6100 was inserted into the 3′-terminal region of In1774 Tn6849 . Tn6830 belonged to the Tn4651 (Tsuda et al, 1989) subgroup of Tn3-family unit transposons, and it highly resembled Tn6489b (Jiang et al, 2020): Tn6830 and FIGURE 4 | Organization of four related IMEs Tn6852, Tn6853, Tn6854, and Tn6855. Genes are denoted by arrows.…”
Section: Comparison Of Five Related Unit Transposons Tn1403 Tn6846 mentioning
confidence: 99%
See 1 more Smart Citation